Pengaruh Struktur Modal, Keputusan Investasi, dan Profitabilitas terhadap Nilai Perusahaan - agus purnomo; nurdiawansyah nurdiawansyah; Indriyani puji astuti (Jurnal Akuntansi dan Keuangan, 2021)
The company value is also described as the actual condition of the company, if the company value is high, investors are willing to invest in the company. The problem that the researchers found was related to company value, namely Indonesian coal companies whose profits decreased in 2018 and 2019. The reason for the decline in profits was the excess supply of coal in the global market. The purpose of this study was to determine the effect of capital structure, investment decisions and profitability of coal companies listed on the IDX on firm value. The total population obtained was 25 coal companies, and the sample selection was by purposive sampling so that the number of samples obtained was 19 companies. This study uses multiple linear regression as a technique and uses SPSS version 20. This study shows that DER has no effect on PBV, PER and ROE have an effect on PBV.